'n Paradigma vir Gereformeerde teologiese wetenskapsbeoefening - ’n voorstel - Deventer, Hans J. M. van (Koers, 1996)
A paradigm for practising Reformed theology - a proposal In the present article the term paradigm, as used in theology, is outlined. The existing paradigms within theology are investigated and it is indicated that the view of Scripture serves as a basic premise in each paradigm. It is further shown that paradigm (view of Scripture) and method (interpretation of Scripture) need not be in tandem. This means that theology can be practis ed within a certain paradigm by using a number of methods. These results are applied to the Faculty of Theology of the "PU vir CHO".